Interleukin-25-Mediated-IL-17RB Upregulation Promotes Cutaneous Wound Healing in Diabetic Mice by Improving Endothelial Cell Functions - Zhang, Fang; Liu, Ye; Wang, Shiqi; Yan, Xin; Lin, Yue; Chen, Deyan; Tan, Qian; Wu, Zhiwei (Frontiers in Immunology, 2022)
Diabetic foot ulcer (DFU) frequently leads to non-traumatic amputation and finally even death. However, the mechanism of DFU is not fully understood. Interleukin 25 (IL-25), an alarmin cytokine that responds to tissue injury, has been reported to participate in tissue regeneration and maintaining glucose homeostasis. However, the role of IL-25 in diabetic wound healing remains unknown. Here, we showed that interleukin 17 receptor B (IL-17RB), the functional receptor of IL-25, was significantly inhibited in the wound skin of both diabetic patients with DFU and streptozotocin (STZ)-induced diabetic mice. Topical administration of recombinant IL-25 protein improved angiogenesis and collagen deposition in the wound bed and thus ameliorated delayed diabetic wound healing. IL-25 increased endothelial-specific CD31 expression in diabetic wounds and exogenous IL-25 protected endothelial cells from high glucose-impaired cell migration and tube formation in vitro. We further revealed that IL-25-mediated-IL-17RB signaling rescued the downregulation of Wnt/β-catenin pathway both in vivo in diabetic mice and in vitro in HUVECs and induced the phosphorylation of AKT and ERK 1/2 in HUVECs under high glucose conditions. This study defines a positive regulatory role of IL-25-mediated-IL-17RB signaling in diabetic wound healing and suggests that induction of IL-25-mediated-IL-17RB signaling may be a novel therapeutic strategy for treating poor healing diabetic wounds.